Refleksi Teologis Gereja Dan Kewirausahaan Jemaat Di Masa Pandemik Coronaviruses Disease 2019 - Roedy Silitonga; Janice Veronica; Timothy Malvin; Hans Christian (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
The church conducts entrepreneurship for the congregation and the community as one of the fulfillment of cultural mandates. One form of church social service is congregational entrepreneurship during the COVID-19 pandemic. The impact of the pandemic has made it difficult for the congregation to meet the needs of daily life. Therefore, the church as an institutionalized individual and community is responsible for carrying out concrete social services through entrepreneurship. This research is a theological response for the church to address the pandemic conditions specifically related to entrepreneurship. This paper uses the literature study method and theological reflection approach. The results of this study are the formation and increase of entrepreneurship managed by congregations and churches in the COVID-19 pandemic area.